Green Marketing Model in Developing Bidadari Waterfall Nature Tourism in Canti Village, South Lampung Regency - Hujaimatul Fauziah; Iwan Zulfikar (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study aims to develop and test an integrated, local wisdom-based green marketing model for sustainable nature tourism at Bidadari Waterfall in Canti Village, South Lampung Regency. Unlike prior studies treating green marketing, digital marketing, environmental awareness, regulation, and local wisdom separately, this research integrates them into a unified explanatory model and positions digital marketing as a mediating variable between green marketing and sustainable tourism. Quantitative explanation was applied using Structural Equation Modeling–Partial Least Squares SEM-PLS. Data were collected from 154 respondents comprising residents, Pokdarwis administrators, and domestic tourists through purposive sampling. The research instrument was adapted from previous studies and contextualized to village-based waterfall tourism. The results show that environmental awareness regulation and local wisdom have significant positive effects on green marketing, with local wisdom being the strongest determinant. This indicates the importance of cultural values and community-based ecological ethics in shaping sustainable tourism marketing. Green marketing influences digital marketing and sustainable tourism, while digital marketing partially mediates the relationship. These findings confirm that sustainable tourism development requires an integrated approach combining ecological awareness, regulatory support, local culture, green value creation, and digital communication. The study contributes to the green marketing literature by integrating local wisdom and digital mediation and proposes the Canti Green Tourism Marketing Model.